Gamma Ray Buildup Factor for Finite Media in Energy Range (4-10) MeV for Al and Pb. - Al-Ani, Laith A; Goarge, Loay E; Mahdi, Marwa S (Al-Nahrain Journal of Science, 2018)
A computer program based on Monte Carlo method had been designed and written in visual basic computer language and utilized for simulating the classic problem of gamma ray beam incident on finite plane slabs of absorbing materials. The source geometry adopted in this program is plane normal source. Dose buildup factor of gamma photons in the absence and presence pair production effect have been calculated in the energy range (4-10) MeV for Aluminum and Lead up to 5 mean free path thickness. Dose buildup factor in the presence of pair production is higher than dose buildup factor in the absence of pair production effect. The deviation between the values of dose buildup factor in the presence and absence pair production is increased when the energy is increased within the studied energy range because the cross section for pair production is increased within the studied energy range.